AB1112 Datanetwork rheuma 4.0 – real world data from private practice. (15th June 2017) - Kleinert, S; Schuch, F; Späthling-Mestekemper, S; Feuchtenberger, M; Kuhn, C; Welcker, M
Abstract : Background: The datanetwork Rheuma 4.0 (DNR_4.0) is a consortium of 5 internistic-rheumatologic specialized practices. Patient data that were collected routinely will be pooled pseudonymized (e.g. via RheumaDok) and will be made available to answer numerous healthcare- and scientific research questions. Methods: The participating centres document the following data in specific rheumatologic data documentation systems (RheumaDok, Emil, DocuMed.rh). These data will be routed automatically to the data base of the DNR_4.0 via a prespecified interface and can be used for certain research areas: Diagnosis (by rheumatologist (R), anamnesis (R), medication (R), morning stiffness (R, patient (P)), scores like RADAI (R, P), DAS28 (R), BASDAI (P), BASFI (P), quality of life (R, P). Also prespecified laboratory measures (R) like ESR, CRP etc. can be collected automatically. Patient reported Outcomes (PROs) that were entered via mobile applications like RheumaLive and AxSpALive can be collected in certain intervalls and be sent encrypted into the medical office data base. The data entered by patients will be screened by the rheumatologist or nurse and will be stored in the underlying data base. Clinical data that are collected during regular F2F-appointments will be stored together with the PROs according to a specific period of time. Results: The datanetwork Rheuma 4.0 (DNR_4.0) is an association of 5 internistic-rheumatologic specialized practices. By the automated documentation of PROs (patient) and medical measures (rheumatologist) in an underlying data base, scientific and health care real worl data can be collected without extra workload or time requirements. These data are specific and different from data collected by other centres. In principal, the extension of the group to increase the number of participating centres is easily possible because the interface is an "open system". This allows to build an automised collecting, big and representative data base. Now pooled data sets of 18.000 patients are available in the data base. In a first step, quality and the completeness of the existing data sets will be evaluated and the daily documentation routines will be described. Anonymised statistical analysis of the pooled data sets of the rheumatologic centres will allow to gain knowledge in respect to health care research of the own working group and external interested parties like research groups, sick funds, insurance companies and companies. Conclusions: The german biologic registry Rabbit and the "Core documentation" data base deliver valid data about the safety and efficacy of rheumatologic medication. The datanetwork Rheuma 4.0 will make a valuable contribution – especially in conjunction with apps of patient's self management like RheumaLive and AxSpALive – to health care research, therapeutic strategies and clinical questions from daily practice. Acknowledgements: RheumaLive and AxSpALive werde developed by Starhealth GmbH on behalf of UCB Pharma GmbH. Disclosure of Interest: S. Kleinert Speakers bureau: UCB, F. Schuch Speakers bureau: UCB, S. Späthling-Mestekemper Speakers bureau: UCB, M. Feuchtenberger Speakers bureau: UCB, C. Kuhn: None declared, M. Welcker Speakers bureau: UCB